Comparative Legal Study on Gender Equality and Female Leadership in Indonesian and Dutch Higher Education - Suhartono, Rizki Mustika; Mashendra, Mashendra; Ribeiro, Leonito; Suhartono, Mutia Aprilia; Rachman, Sulyanti (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This article explores the ongoing global issue of gender equality and female leadership in higher education. While many countries have adopted gender-inclusive policies, practical implementation remains inconsistent. Western countries such as the Netherlands demonstrate measurable progress, whereas Southeast Asian nations like Indonesia face persistent cultural and structural barriers. Prior studies tend to focus on sociological or institutional aspects, with limited comparative legal analysis.Purposes of the Research: The aim of this study is to explore and compare legal guarantees, national policies, and institutional practices that affect women's access to leadership positions in universities in Indonesia and the Netherlands, to identify legal barriers and propose normative strategies in support of more inclusive academic leadership.Methods of the Research: This research employs normative legal methods with a comparative law approach. It analyzes constitutional provisions, gender equality statutes, higher education regulations, and leadership policies from both countries, supported by literature review and document study.Results of the Research: The findings show that the Netherlands has established stronger legal enforcement for gender equality in academic leadership through comprehensive legal instruments and monitoring mechanisms. In contrast, Indonesia, despite recognizing gender equality in its legal framework, lacks effective implementation mechanisms. The novelty of this research lies in its comparative legal perspective and its recommendation to integrate normative legal approaches with contextual cultural values to promote inclusive governance in higher education.